Gold and Nickel Extended Thiophenic-TTF Bisdithiolene Complexes - Silva, Rafaela; Vieira, Bruno; Andrade, Marta; Santos, Isabel; Rabaça, Sandra; Lopes, Elsa; Coutinho, Joana; Pereira, Laura; Almeida, Manuel; Belo, Dulce (Molecules (Basel, Switzerland), 2018)
Gold and nickel bisdithiolene complexes with methyl and tert-butyl substituted thiophenetetrathiafulavalenedithiolate ligands (α-mtdt and α-tbtdt) were prepared and characterized. These complexes were obtained, under anaerobic conditions, as tetrabutylammonium salts. The diamagnetic gold monoanion (n-Bu4N)[Au(α-mtdt)2] (3) and nickel dianionic species (n-Bu4N)x[Ni(α-mtdt)2] (x = 1,2) (4) were similar to the related non-substituted extended thiophenic-TTF (TTF = tetrathiafulvalene) bisdithiolenes. However the introduction of the large, bulky substituent tert-butyl, led to the formation of a Au (I) dinuclear complex, (n-Bu4N)2[Au2(α-tbtdt)2] (5). The neutral methyl substituted gold and nickel complexes were easily obtained through air or iodine exposure as polycrystalline or amorphous fine powder. [Au(α-mtdt)2] (6) and [Ni(α-mtdt)2] (7) polycrystalline samples display properties of a metallic system with a room temperature electrical conductivity of 0.32 S/cm and ≈4 S/cm and a thermoelectric power of ≈5 µV/K and ≈32 µV/K, respectively. While [Au(α-mtdt)2] (6) presented a Pauli-like magnetic susceptibility typical of conducting systems, in [Ni(α-mtdt)2] (7) large magnetic susceptibilities indicative of high spin states were observed. Both electric transport properties and magnetic properties for gold and nickel [M(α-mtdt)2] are indicative that these compounds are single component molecular conductors.